Administración pública y su relación en la gestión de cambio organizacional del Gad municipal Quevedo, período 2023 - 2024 - Jerez López, Karen Melissa (2025)
Effective public management is largely based on effective and interdepartmental communication. Therefore, the present research entitled Public Administration and its relationship in the Organizational Change Management of the Municipal GAD of the Quevedo canton, period 2023-2024, had as its main objective to analyze the relationship between public administration and organizational change management in the Municipal GAD of Quevedo in the period 2023–2024. This research was developed under a methodology with a mixed approach (qualitative and quantitative), the inductive method was used, which allowed to determine general conclusions. It was considered that the Municipal GAD has a population distributed by one thousand one hundred and fifty public servants, and three departmental heads. Interviews were applied to each of the departmental heads and public servants, and surveys were applied to the labor staff of the different departments (administrative area). The main results determined that there are significant challenges in the effective implementation of new practices, since 37.2% of the surveyed staff pointed out the "lack of clear information" as the main element that causes resistance, followed by the "lack of training or formation" with 29.5%. Concluding that, leadership exerts a beneficial effect on the processes of organizational change in the Quevedo Municipal GAD, however, there are also possibilities for improvement in terms of management support and staff motivation.